The Correlation Between Self-Confidence And Students’ Speaking Ability At The Third-Year Students Of Madrasah Aliyah Al-Qasimiyah Sorek Satu - Hafizhah Arsad; Mahdum Mahdum; Dahnilsyah Dahnilsyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The purpose of this study is to find out is there any correlation between self-confidence and the speaking ability at the third year students of Madrasah Aliyah Al-Qasimiyah Sorek Satu. This research will look at the relationship between students' speaking ability and their sense of self-confidence. According to Hatch and Lazaraton (1991), correlation studies are used to assess the degree of relationship between two variables in this research, these variables include students' speaking abilities and self-confidence. Madrasah Aliyah Al-Qasimiyah's self-confidence, the highest score for third year students of Madrasah Aliyah Al-Qasimiyah is 98.2%, they have very high self-confidence, where students hope to excel in this class. which refers to the course/class content. It can be concluded that students have a high level of general self-confidence in themselves and their abilities. The research results show that speaking skills and self-confidence are moderately and positively correlated and have a significant impact on teachers and administrators of Madrasah Aliyah Al-Qasimiyah Sorek Satu and other similar institutions. These results imply that programs that focus on increasing students' self-confidence may also benefit their speaking abilities. These findings emphasize the importance of these factors and imply that interventions that focus on both factors may benefit students' academic success and personal growth.